Morphological plasticity of human melanoma cells is determined by nanoscopic patterns of E- and N-cadherin interactions - Amschler, Katharina; Spatz, Joachim P. (The journal of investigative dermatology, 2019)
Loss of E-cadherin and concomitant upregulation of N-cadherin is known as the cadherin switch, and has been implicated in melanoma progression. Mechanistically, homophilic ligation of N-cadherin-expressing melanoma cells with N-cadherin presented within the microenvironment is thought to facilitate invasion. However, the biophysical aspects governing molecular specificity and function of such interactions remain unclear. By using precisely defined nano-patterns of N- or E-cadherin (with densities tunable by more than one order of magnitude from 78 to 1,128 ligands/μm2), we analyzed adhesion and spreading of six different human melanoma cell lines with distinct constitutive cadherin expression patterns. Cadherin-mediated homophilic cell interactions (N/N and E/E) with cadherin-functionalized nano-matrices revealed an unexpected functional dichotomy inasmuch as melanoma cell adhesion was cadherin density-dependent, while spreading and lamellipodia formation were independent of cadherin density. Surprisingly, E-cadherin-expressing melanoma cells also interacted with N-cadherin-presenting nano-matrices, suggesting heterophilic (N/E) interactions. However, cellular spreading in these cases occurred only at high densities of N-cadherin (i.e., >285 ligands/μm2). Overall, our approach using nano-patterned biomimetic surfaces provides a platform to further refine the roles of cadherins in tumor cell behavior and it revealed an intriguing flexibility of mutually compensating N- and E-cadherin interactions relevant for melanoma progression.
Published online 28 October 2018; corrected proof published online 20 December 2018
Gesehen am 04.09.2019